Afibrinogenemia caused by a novel homozygous missense mutation, FGB p.Cys241Tyr, in a male patient with recurrent intracranial bleeding: case report and review of literature. Issue 1 (27th November 2020) - Zdziarska, Joanna; Wypasek, Ewa; Iwaniec, Teresa; Vilar, Rui; Neerman‐Arbez, Marguerite; Undas, Anetta
Abstract: Introduction: Congenital afibrinogenemia is a severe bleeding disorder, sometimes manifesting as thrombosis and/or pregnancy complications. Intracranial haemorrhage (ICH) constitutes the major cause of death in this disease. Methods: We present the case of a male patient with congenital afibrinogenemia, who presented with recurrent intracranial hemorrhages, despite prophylactic fibrinogen substitution. We also review the literature for the risk of intracranial hemorrhages in afibrinogenemia. Result: Molecular analysis revealed a novel homozygous missense mutation in FGB exon 5, p.Cys241 Tyr, that was named "Fibrinogen Krakow V". Discussion and conclusion: Intracranial hemorrhage is a severe manifestation of afibrinogenemia, also in children. The clinical presentation of afibrinogenemia is variable. Fibrinogen substitution carries a risk of thrombotic complications.